Анализ чувствительности конечномерных и континуальных моделей структурно связанных систем - Назаренко, Сергей Александрович (НТУ "ХПИ", 2007)
Coupled-field analyses are useful for solving problems where the coupled interaction of phenomena from various disciplines of physical science is significant. There are basically two methods of coupling distinguished by the finite element formulation techniques used to develop the matrix equations. Complicated finite-element models sensitivity analysis methods for structurally connected systems are given in this article.
Keywords: комплексное моделирование конструкций; виртуальные испытания; функционалы качества конструкций; режимы нагружения